2013
DOI: 10.1109/tbme.2013.2247401
|View full text |Cite
|
Sign up to set email alerts
|

Reference-Based Source Separation Method For Identification of Brain Regions Involved in a Reference State From Intracerebral EEG

Abstract: In this paper, we present a fast method to extract the sources related to interictal epileptiform state. The method is based on general eigenvalue decomposition using two correlation matrices during: 1) periods including interictal epileptiform discharges (IED) as a reference activation model and 2) periods excluding IEDs or abnormal physiological signals as background activity. After extracting the most similar sources to the reference or IED state, IED regions are estimated by using multiobjective optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We find the source spatial map in four steps. First by using a referenced based source separation (R-SS) method (Samadi et al, 2013) the time courses of the HCTP sources are estimated, secondly the forward model is projected on the HCTP source space and thirdly, the spatial map of each HCTP source is estimated using a sparse decomposition method. Finally, Pareto optimization method is used to find the active regions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find the source spatial map in four steps. First by using a referenced based source separation (R-SS) method (Samadi et al, 2013) the time courses of the HCTP sources are estimated, secondly the forward model is projected on the HCTP source space and thirdly, the spatial map of each HCTP source is estimated using a sparse decomposition method. Finally, Pareto optimization method is used to find the active regions.…”
Section: Methodsmentioning
confidence: 99%
“…We call them highly correlated with interested task paradigm sources (HCTP sources). The HCTP source space is found by applying the reference-based source separation (R-SS) method proposed in (Samadi et al, 2013). R-SS is a semi-blind source separation method which extracts the discriminating sources of two data groups, one group being related to the task of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we want to test if a priori information on the spike-like subspace can be used in the denoising process. For EEG signals, it has been previously shown that different assumptions about sources of interest, such as spatial constraints [14], locations of known sources [15], shape and latency of the signal of interest [16] and time support of spikes [17], can be considered in semi-blind or constrained source separation methods. In this paper, we use the timing information of the epileptic interictal sources (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These preprocessing stages consist of the detection and clustering of the epileptic spikes involved in each source of interest. It should be mentioned that a GEVD-based method was previously proposed in [17] in order to determine epileptic regions from epileptic intracerebral EEG signals. This method has a manual preprocessing stage to extract periods including interictal epileptiform discharges.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main research topics on the application of ICA to EEG signals is the dynamic modeling of brain oscillations in humans [230,189,109,61] and lab rats [232,10]. This research attempts to combine the advantages of independent component analysis with the capabilities of certain dynamic models to deal with the temporal variability of the EEG.…”
Section: Application On Electroencephalographic Signalsmentioning
confidence: 99%